COVID-19, SIXTEEN MONTHS INTO THE PANDEMIC: A NARRATIVE REVIEW - Saumtally, Hishaam; Cassidy, Sheena; Shankar Lal,; Khan, Ehtesham (Journal of Ayub Medical College Abbottabad, 2021)
COVID-19, the disease caused by the newly-discovered SARS-CoV-2 virus, has quickly spread from China throughout the world since January 2020. Its potential severity, despite in a minority of cases, has paralysed healthcare systems struggling for adequate resources, as well as entire nations often forced to adopt radical measures, such as lockdowns and surveillance, to contain the disease and restrict its spread. Initially presenting as a respiratory infectious disease, it can not only progress to an acute respiratory distress syndrome, but also have multisystemic consequences. There are many proving theories as regards to the pathophysiology and there are currently no proven definitive treatments. Due to its high transmissibility and the risk of infecting healthcare workers, hospitals also had to rethink their organisation. We have completed a literature review of the sixteen months of the pandemic, with attention to pathophysiology, key epidemiological concepts, hospital organisation, critical care considerations, and finally current and prospective treatments.